2019
DOI: 10.1016/j.coastaleng.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined wave-current induced excess pore-pressure in a sandy seabed: Flume observations and comparisons with theoretical models

Abstract: Waves are coexisting with currents in coastal zones; nevertheless, previous experimental studies for excess pore-pressure responses in a porous seabed were predominantly limited to the wave-only condition. In this study, the combined wave-current induced excess porepressures in a sandy seabed were experimentally simulated with a specially-designed flume, which can concurrently generate periodic waves and a following/opposing co-directional current. The effect of a current on the wave profile is firstly examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
6
36
0
Order By: Relevance
“…An alternative hybrid foundation system comprising a monopile and a bearing plate (or skirted footing) has been demonstrated to enhance the lateral bearing capacity compared with a monopile [96][97][98][99]. Nevertheless, the enhanced capacity of the hybrid foundation largely relies on the proper interaction between the bearing plate and the soils at the shallow zone of the seabed, where local scour and wave-induced pore pressure could occur [100][101][102][103][104][105][106][107][108]. The extent of local scour and scour effects on both the bearing capacity and natural frequency of a hybrid monopile need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hybrid foundation system comprising a monopile and a bearing plate (or skirted footing) has been demonstrated to enhance the lateral bearing capacity compared with a monopile [96][97][98][99]. Nevertheless, the enhanced capacity of the hybrid foundation largely relies on the proper interaction between the bearing plate and the soils at the shallow zone of the seabed, where local scour and wave-induced pore pressure could occur [100][101][102][103][104][105][106][107][108]. The extent of local scour and scour effects on both the bearing capacity and natural frequency of a hybrid monopile need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liao et al [32] proposed coupling models for residual seabed liquefaction subject to combined wave and current loading. Although numerous theoretical studies have been carried out since 2012, only two experimental studies for the wave (current)-induced oscillatory soil response are available in the literature [33,34]. These studies were used for the validation of the present model.…”
Section: Introductionmentioning
confidence: 99%
“…When excess pore pressure exceeds the overburden pressure, the effective stresses of the soil skeleton vanish, and the soil behaves like a liquid. This phenomenon is referred to as liquefaction, and it can lead to the collapse of the marine structure [5,6]. Smith and Gordon [7] reported that the failure of marine structures was predominantly caused by wave-induced seabed instability rather than structural deficiencies.…”
Section: Introductionmentioning
confidence: 99%